Ability of benthic oligochaetes to bury microplastics in aquatic bottom sediments - Frank, Yuliya A.; Vorobiev, Danil S.; Vorobiev, Egor D.; Samarinova, Alisa A.; Antsiferov, Dmitry V.; Strezov, Vladimir (Science of the total environment)
Benthic organisms, including freshwater oligochaetes Tubificidae, contribute to redistribution of microplastics (MPs) in aquatic bottom sediments. In this work quantitative data was obtained in the model experiment characterizing the rate of polypropylene (PP) microparticle burial under the action of Tubifex tubifex worms in silty freshwater bottom sediments. The average rate of microplastic (MP) deposition in presence of worms was 4.14±1.29 cm year-1 compared to 0.73 cm year-1 under control conditions. Bioturbation due to the motion of worms in the sediments and their respiratory movements is the leading factor in the burial of MP particles. The study confirmed that bottom sediments accumulate deposited MPs, including those with the participation of macrozoobenthos organisms.